Glossopharyngeal neuralgia due to exposed glossopharyngeal nerve post tonsillectomy and transoral styloidectomy - Mahalingappa, Ajith Keragodi; Gupta, Richa; Ramakrishnan, Swathi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Glossopharyngeal neuralgia (GN) is a rare facial pain syndrome, characterized by paroxysm of excruciating radiating pain in the sensory distribution of the auricular and pharyngeal branches of glossopharyngeal and vagus nerves. In relation to the tonsil, the glossopharyngeal nerve passes deep to the styloid process and related muscles attaching to styloid process. The lingual branch of the glossopharyngeal nerve provides sensation to the posterior tongue and enters the tongue base by traveling through the constrictor muscles in the area of the lingulotonsillar sulcus. Post tonsillectomy fossa with exposed nerve causing intractable pain is a rare entity. We report a case of 64 year male patient, post tonsillectomy and transoral styloidectomy, with complaint of severe throat pain on left side for 2 years, radiating upwards to the ipsilateral ear, face and eye. Glossopharyngeal nerve and its branches were found exposed in the posterior and inferior aspect of tonsillar bed. Surgical resection of exposed glossopharyngeal nerve and its branches was carried out in view of failure to respond to oral carbamazepine. Patient was symptom free during 10 months of follow up visit. GN is a rare condition following tonsillectomy and styloidectomy. Radical dissection of tonsillar bed during tonsillectomy and not suturing tonsillar bed properly after styloidectomy can lead to exposure of glossopharyngeal nerve and its branches, resulting in intractable GN.